Pengaruh Tata Kelola Komunikasi terhadap Efektivitas Kinerja Pegawai di Madrasah Tsanawiyah Al-Amanah Bogor - Namira, Namira Fauziah; Nabilah Sri Rejeki; Muhammad Rendi Ramadhani (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
The success of a performance in educational institutions can be seen from the existence of good cooperation and communication climate between roles. Good education will certainly produce a superior and quality generation, so to achieve this goal there needs to be cohesiveness and mutual involvement of various parties related to the school. This study aims to analyze the urgency of communication governance so that it influences the effectiveness of employee performance at MTs Al-Amanah Bogor. The method of collecting data from this study is using a qualitative descriptive approach with observation and interview techniques as well as citing several discussions related to research from several sources; namely journals, books, articles, and others. As for the results of this study, that communication governance greatly influences the effectiveness and productivity of employee performance and the communication governance system that is implemented is quite good. This is influenced by a two-way communication system. So that it shows openness and minimizes the possibility of miss communication.